Plasma Dynamic Synthesis of Metal Oxides in a Carbon Dioxide Medium in the Ti–O and Fe–O Systems; Inorganic Materials; Vol. 14, No. 3 - Shanenkov I. I. Ivan Igorevich; Sivkov A. A. Aleksandr Anatolyevich; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich; Nikitin D. S. Dmitry Sergeevich; Tabakaev R. B. Roman Borisovich (2023, 2023)
Title screen